2009
DOI: 10.1016/j.geoderma.2009.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Amendments with organic and industrial wastes stimulate soil formation in mine tailings as revealed by micromorphology

Abstract: Amendments with organic and industrial wastes stimulate soil formation in mine tailings as revealed by micromorphology Zanuzzi, A.; Arocena, J.M.; van Mourik, J.M.; Faz Cano, A. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 31 publications
2
53
1
8
Order By: Relevance
“…Incorporating organic amendments will usually increase saturated hydraulic conductivity (Gupta et al 1977;Leroy et al 2008a) although contrasting and inconclusive results have often been reported (Khaleel et al 1981;Zebarth et al 1999;Schneider et al 2009). The very high variability of hydraulic conductivity may make it difficult to detect induced effects from organic amendments under field conditions.…”
Section: Water Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating organic amendments will usually increase saturated hydraulic conductivity (Gupta et al 1977;Leroy et al 2008a) although contrasting and inconclusive results have often been reported (Khaleel et al 1981;Zebarth et al 1999;Schneider et al 2009). The very high variability of hydraulic conductivity may make it difficult to detect induced effects from organic amendments under field conditions.…”
Section: Water Movementmentioning
confidence: 99%
“…In southeastern Spain, Zanuzzi et al (2009) added pig manure and sewage sludge in combination with a blanket application of marble wastes aimed at building soil organic matter and accumulating calcite in mine tailings. The acidity of the tailings combined with low rainfall in the study area precipitated secondary calcite as infillings within the 0 to 4 cm surface layer.…”
Section: From Larney Et Al (2003a)mentioning
confidence: 99%
“…De fato, alguns trabalhos já foram conduzidos objetivando-se a correção de pH de solos acidificados em áreas mineradas em que a utilização de pó de mármore foi eficiente na redução de metais tóxicos, não apenas do Al, mas também As, Cu, Pb, Zn e Cd (Fernández-Caliania & Barba-Briosob, 2010). Em associação com compostos orgânicos esses materiais podem, inclusive, contribuir para a formação de solo em áreas completamente degradadas (Zanuzzi et al, 2009).…”
Section: Influência Das Doses Aplicadasunclassified
“…High incidences of wind and water erosion events negatively affect soil, water, vegetation, fauna, and human populations in the surrounding areas (Zanuzzi et al, 2009) (Bradshaw and Johnson, 1992). Organic waste such as sewage sludge and animal manure can be used as nutrient sources which stimulate the formation of aggregates (Zanuzzi et al, 2009)…”
Section: Introductionmentioning
confidence: 99%